Simulation of Landcover Change Influences for Water Availability Using a Regional Atmospheric Model - Edvin Aldrian (Pusat Penelitian dan Pengembangan BMKG, 2007)
A study of the landcover change impact on water budget has been done using a mesoscale climate model. A prestine lake catchment of Lake Poso in Central Sulawesi Province has been used for this study. A scenario for deforestation that change forest into savannah was performed for the dry period from July to December 2005 to simulate the severest possible scenario. The results show increase risks of flood during wet season and risks of drought during the dry season with highest increase of surface runoff up to 18% and decrease up to 10%. Meanwhile, the underground runoffincrease during wet season up to 17% and decrease up to 10% during the dry season. This study may suitable for the climate change impact study and to simulate the land degradation due to ever increasing deforestation and land clearing.